Rola cierpienia w życiu człowieka w świetle listów Zygmunta Krasińskiego - Galek, Czesław (Studia Pastoralne, 2026)
Zygmunt Krasiński (1812–1859) was one of the greatest Polish Romantic poets. The objective of this article is to present his views on suffering in light of his letters written to various addressees. The article describes the problems of the causes and effects of suffering and the sense of suffering, as well as the causes and effects of man’s happiness. Krasiński saw the ultimate cause of suffering in the original sin, which had introduced disintegration in the whole created world, also in man. He viewed suffering in light of the mystery of the passion, death and resurrection of Jesus Christ, seeing it as a means of man’s spiritual development and his eternal salvation. Even though man cannot become fully happy on earth, he should aim at making others happy. The fullness of happiness can only be reached in life after death, when man will become united with God.